Coffee Agroforestry and the Food and Nutrition Security of Small Farmers of South-Western Ethiopia - Jemal, Omarsherif Mohammed; Callo-Concha, Daniel; van Noordwijk, Meine (Frontiers in Sustainable Food Systems, 2021)
Agroforestry generally contributes to rural food and nutrition security (FNS). However, specialization on commodity-oriented agroforestry practices or management strategies can weaken local food sourcing when terms of trade fluctuate, as is the case of coffee in Ethiopia. Hence, this study assessed the trade-offs that smallholder farming households in south-western Ethiopia face between growing coffee in agroforestry systems and their food and nutrition security based on home production as well as markets. Data collected from 300 randomly selected households included: (i) attributes of agroforestry practices(AFP) and plants: structure, use type, edibility, marketability, nutritional traits, and (ii) the householders'FNS attributes: food security status, nutritional adequacy, and nutritional status. Data were collected both in food surplus and shortage seasons, during and after coffee harvesting. Within these data, the number of plant species and vegetation storeys were significantly correlated with household food access security in both seasons and for all AFP identified, i.e., homegarden, multistorey-coffee-system, and multipurpose-trees-on-farmlands. The number of stories in homegardens and the richness of exotic species in multipurpose-trees-on-farmlands were significantly correlated with the biometric development of children below 5 years old during the shortage season. The richness of ‘actively-marketed’ species in all AFP correlated with the food access security of the household, except in the multistorey-coffee-system, oriented to coffee production. Also, families that cultivate all three AFP showed significantly higher household diversity dietary during the shortage season. We conclude that no single AFP can secure FNS status of the households by itself, but the combination of all three can. Household and individual dietary scores were positively correlated with the AFP diversity-attributes, especially in the shortage season. Thus, the diversity of useful groups of plant species deserves to be promoted for instance by enriching AFP with edible and storable crops needed during the shortage season.